DIVERSI DAN RESTORATIVE JUSTICE TERHADAP ANAK BERKONFLIK DENGAN HUKUM DALAM PELAKSANAAN SISTEM PEMASYARAKATAN - Rachmayanthy . (Universitas Pamulang, 2016)
Juvenile in conflict with the law according to Indonesian constitution number 12 years 2012 about Junenile Justice System are Children, which have riched 12 years old and under 18 years old suspected crime. Law enforcement for juvenile suspectible of negative impact cause by the judicial process, such as Stigma. Community has tend to “judge” that they are naughty children/ criminal and worthly to be dissociated from society, or even worthy imprisoned. Therefore, dissociate juvenile from judicial process (especially imprisoned) is more preferred. Deinstitutionalization for juvenile in conflict with the law is one of strategic policy for children best interest. Therefore, detention and imprisoned were the last attempt in consider of sociological and psychological impact. Best solution in juvenile case were diversion and restorative justice. Diversion according to Indonesian Constitution is diversion settlement of juvenile case from criminal justice process to other. While, restorative justice is a process when every body/ side that involved are gathered to talk about the win win solution of the problem which best for nowadays and future interest. Correctional is a system and subsystem is every stages of criminal justice system, especially the criminal justice of juvenile. The stages began from pra adjudication, adjudication (by Bapas and LPAS) and post adjudication stage (by LPKA and Bapas). Balai Pemansyarakatan or we call it Bapas is a subsystem of correction which has role from beginning of criminal justice process. Its function is pra adjudication and adjudication stages were accompaniment, guiding, supervision of diversion criminal justice of juvenile and also restorative justice. In post adjudication stage, the principle of restorative justice is still needed with LPKA, Bapas and other are involved for the implementation.Keywords: Juvenile in conflict with the law, Diversion Restorative justice, Correction